PENGARUH URBANISASI TERHADAP TUMBUHNYA RUMAH BEDENG DI SEMARANG - Nandang, Debagus (TATAL, 2011)
Urbanization is a global phenomenon, which is a lame one ofimpact the provision of urbanservices , speciallyhousing and settlements . Not one city in the world who escaped from the clutter. Indeveloped and developing countries, the city has been broken due to urbanization. Berduyunnya people tothe city all of a sudden, especially since the era of industrialization, are the main cause that makes the citynot ready to face reality. Urbanization in cities of developing countries the problem is more complicated,because population growth is happening faster than in developed countries.The growth of cities that are not predictable cause various problems Development of the city, such as highlevels of density of buildings, insufficient availability of infrastructure and urban facilities (urban facilities),rapid growth and development of slums in the center city and also uncontrolled physical changes of thecity. Those who are less fortunate get jobs and decent incomes, quite content to be in town though it mustbe domiciled metropolitan area of settlements that lack infrastructure as in most of those found in urbanareas. They generally live around the factory / industry in a relatively close radius to save on transportationcosts. Another form of settlement between the houses plot with rental fees are relatively inexpensive,because workers are generally hired by industrial plants with minimal income.Key words: Urbanization, slums, no permanent home